TATA KELOLA BAITUL MAAL WA TAMWIL (BMT) BERBASIS PRINSIP 6C DAN MODAL SOSIAL : STUDI PADA BMT MEKAR DAWAH - Syafik Wildan Afif; Darwanto Darwanto (al-Uqud : Journal of Islamic Economics, 2017)
The study  analyzes the role of governance BMT Mekar Da'wah and social capital in processing Musharaka financing. This study uses qualitative method . The source of data and information are  employees in BMT Mekar Dawah such as the branch manager, head of the division of financing, marketing head of the division and customers of  BMT Mekar Dawah as key persons. Collecting data uses purposive sampling technique. The data are primary data that based on interviews with key persons associated with the research. The analysis technique used is the interactive model. The results showed that corporate governance at BMT Mekar Da'wahs 6C (character, capacity, capital, collateral, condition of economy and constrain) based on the concept that applied to the collection of information on prospective customers who will conduct financing filings with the provisions. Social capital is owned by BMT Mekar Da'wah is  trust formed by a good relationship  with society as cooperation in several community events. Besides, the shared value formed from their belief to religiosity of people who manage BMT  is also one of social capital.